Design of protein homocystamides with enhanced tumor uptake properties for (19)F magnetic resonance imaging - Chubarov, Alexey S; Zakharova, Olga D; Koval, Olga A; Romaschenko, Alexander V; Akulov, Andrey E; Zavjalov, Evgenii L; Razumov, Ivan A; Koptyug, Igor V; Knorre, Dmitry G; Godovikova, Tatyana S (Bioorganic & medicinal chemistry, 2015)
Straightforward and reliable tools for in vivo imaging of tumors can benefit the studies of cancer development, as well as contribute to successful diagnosis and treatment of cancer. (19)F NMR offers an exceptional quantitative way of in vivo imaging of the infused agents because of the lack of (19)F signals from the endogenous molecules in the body. The purpose of this study is to develop molecular probes with appropriate NMR characteristics and the biocompatibility for in vivo applications using (19)F MRI. We have studied the reaction between perfluorotoluene and homocysteine thiolactone resulting in the formation of N-substituted homocysteine thiolactone derivative. It has been shown that the reaction occurs selectively at the para position. This fluorine-labeled homocysteine thiolactone has been employed for the introduction of a perfluorotoluene group as a (19)F-containing tag into human serum albumin. The modified protein has been studied in terms of its ability to aggregate and promote the formation of free radicals. By comparing the properties of N-perfluorotoluene-homocystamide of albumin with N-homocysteinylated albumin, it has been revealed that blocking of the alpha-amino group of the homocysteine residue in the fluorinated albumin conjugate inhibits the dangerous aggregation process, as well as free radical formation. A dual-labeled albumin-based molecular probe for (19)F MRI and fluorescence microscopy has been obtained by functionalizing the protein with both maleimide of a fluorescent dye and a fluorinated thiolactone derivative. The incubation of cells with this conjugate did not reveal any significant reduction in cell viability with respect to the parent albumin. The perfluorotoluene-labeled albumin has been demonstrated to act as a promising agent for in vivo (19)F MRI.